Knowledge-sharing, control, compliance and symbolic violence - Kamoche, Ken; Kannan, Selvi; Siebers, Lisa Qixun (SAGE, 2014)
Recent developments in control hold that professionals are best managed through normative and concertive as opposed to bureaucratic and coercive mechanisms. This post-structuralist approach appeals to the notion of congruent values and norms and acknowledges the role of individuals’ subjectivity in sustaining professional autonomy. Yet, there remains a risk of over-simplifying the manifestations of such control initiatives. By means of an in-depth case study, this article considers the challenge of implementing a knowledge-sharing portal for a community of R&D scientists through management control initiatives that relied on a blend of presumed ‘peer pressure’ and the rhetoric of ‘facilitation’. Arguing that traditional approaches such as normative/concertive control and soft bureaucracy only partially explain this phenomenon, we draw from Pierre Bourdieu’s concept of ‘symbolic violence’ to interpret a managerial initiative to appropriate knowledge and affirm the structure of social relations through the complicity of R&D scientists. We also examine how the scientists channelled resistance by reconstituting compliance in line with their sense of identity as creators of knowledge.